Podejście prawa izraelskiego do prawa małoletnich do podejmowania decyzji ich dotyczących - Khawaly-Esawi, Rita K (Studia Edukacyjne, 2020)
The purpose of the paper is to examine the attitude of Israeli law towards minors’ participation in making decisions relating to them. This right is expressed in the United Nations Convention on the Rights of the Child which has turned into an international document approved by nations all over the world. The minor’s right to participate in decisions relating to him is enshrined in Section 12 of the United Nations Convention on the Rights of the Child. It is possible to see that the convention recognized the dignity of the person and the human rights of the minor. However, it is willing to grant rights to minors taking into consideration their age and their different stages of development. Sometimes parents focus mainly on their own interest and rights, and thus find it hard to faithfully determine their children’s rights and protect their best interest. If a minor does not have the right to participate in legal proceedings relating to him, he might get hurt. The view which accepts the notion of independent representation of a minor stems from the concept that a minor has rights like adults, and those rights include one to independent representation. Such a right can be practiced when the minor himself, his guardian or lawyer, represents his interests independently from his parents. Israeli law generally does not provide minors with independent rights such as the right to be a part of decision making. However, it does provide minors with rights in specific cases which might be seen as necessary, and there is still considerable space for the personal worldview of the judge. In addition, Israeli law is yet to adequately define the exact role of the legal guardian representing a minor and his methods of operation, and nowadays this duty depends on the personality of a legal guardian and his approach to this duty.